Recent Advances in Intrusion Detection 12th International Symposium, RAID 2009, Saint-Malo, France, September 23-25, 2009, Proceedings - Kirda, Engin; Jha, Somesh; Balzarotti, Davide (Security and Cryptology, 2009)
This book constitutes the refereed proceedings of the 12th International Symposium on Recent Advances in Intrusion Detection, RAID 2009, held in Saint-Malo, Brittany, France, in September 2009. The 17 revised full papers presented together with 16 revised poster papers were carefully reviewed and selected from 59 submissions. The papers are organized in topical sections on anomaly and specification-based approaches, malware detection and prevention, network and host intrusion detection and prvention, intrusion detection for mobile devices, and high-performance intrusion detection.